Catalytic Hydrogenation of Carboxamides with a Bifunctional Cp*Ru Catalyst Bearing an Imidazol-2-ylidene with a Protic Aminoethyl Side Chain - Kawano, Teruhiro; Watari, Ryo; Kayaki, Yoshihito; Ikariya, Takao (Synthesis, 2019)
Synthesis of a Cp*Ru complex bearing an NH2-functionalized N-heterocyclic carbene (C–NH) was achieved by treatment of Cp*RuBr(isoprene) with an equimolar amount of a silver complex, which was generated from Ag2O and 1-(2-aminoethyl)-3-methylimidazolium bromide, in CH3CN at room temperature. The new Cp*RuBr(C–NH) complex showed a higher catalytic performance than the related Cp*RuCl(P–NH) and Cp*RuCl(N–NH) complexes. In the reaction of N-arylcarboxamides, the amine products were obtained in satisfactory yields under mild temperature conditions.
Keywords: ruthenium; hydrogenation; amides; amines; alcohols; N-heterocyclic carbenes